Primary cerebral neuroblastoma: CT and MR findings in 12 cases. - Davis, P C; Wichman, R D; Takei, Y; Hoffman, J C (American Journal of Neuroradiology, 1990)
A retrospective CT, MR, and clinical study was performed in 12 patients, five children and seven adults, with histologically proved primary CNS neuroblastoma. The CT and MR appearances of these neoplasia were more variable than generally recognized. Although seven tumors were predominantly intraparenchymal masses with calcification and cyst formation, five were intra- or juxtaventricular. CT was preferable to noncontrast MR both at initial diagnosis and follow-up for identification of calcification, recurrent tumor at surgical sites, and leptomeningeal disease. Noncontrast MR was useful primarily for localization of peri- and intraventricular lesions. We conclude that primary CNS neuroblastoma has a more variable radiographic appearance than is generally recognized, and that an intra- or periventricular epicenter is common.